ANALISIS SERTIFIKASI PERTANIAN ORGANIK UNTUK MENENTUKAN ASPEK SOSIAL EKONOMI (STUDI KASUS KASUS DI KELOMPOK PANGUDI BOGA, DLINGO-MOJOSONGO, KABUPATEN BOYOLALI) - M.Th. HANDAYANI; KUSRIANI PRASETYAWATI; MAHANANTO MAHANANTO; SUSWADI SUSWADI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2018)
Analysis of Certified Organic Rice Farming Income (Case Farmers Group of Pangudi Boga, Dlingo-Mojosongo District of Boyolali). Pangudi Boga group is engaged in the development of organic rice, necessary to study the analysis of certified organic rice farming income, and social aspect. This study conducted to determine social-economic aspect : the amount of income, the R/C ratio, BEP and social activity at the Farmer Group of Pangudi Boga. Determination respondents income analysis by quota sampling 50% of amount of farmers, and key informants to determine the application of the ICS. The analysis is the farm income, R/C ratio, BEP, and descriptive analysis . The result showed an average cash reached Rp 18.104.171 and the total income reached Rp 16.123.811 per hectare per cropping season. The value of R /C ratio of the total cost was 2.49. The indicates is the certified organic rice farming viable. The social aspect indicates that ICS of Pangudi Boga group carried inspector on all members of farmer and external oversight by LeSos. Suggested to farmers in order to maintain the rice farm is certified organic, farmer groups and ICS. Training of the farmers also need to be done continuosly so that farmers consistent to maintain the certificate.